Complexity of heart rate variability predicts outcome in intensive care unit admitted patients with acute stroke . Issue 1 (21st July 2014) - Tang, Sung-Chun; Jen, Hsiao-I; Lin, Yen-Hung; Hung, Chi-Sheng; Jou, Wei-Jung; Huang, Pei-Wen; Shieh, Jiann-Shing; Ho, Yi-Lwun; Lai, Dar-Ming; Wu, An-Yeu; Jeng, Jiann-Shing; Chen, Ming-Fong
Abstract : Background: Heart rate variability (HRV) has been proposed as a predictor of acute stroke outcome. This study aimed to evaluate the predictive value of a novel non-linear method for analysis of HRV, multiscale entropy (MSE) and outcome of patients with acute stroke who had been admitted to the intensive care unit (ICU). Methods: The MSE of HRV was analysed from 1 h continuous ECG signals in ICU-admitted patients with acute stroke and controls. The complexity index was defined as the area under the MSE curve (scale 1–20). A favourable outcome was defined as modified Rankin scale 0–2 at 3 months after stroke. Results: The trends of MSE curves in patients with atrial fibrillation (AF) (n=77) were apparently different from those in patients with non-AF stroke (n=150) and controls (n=60). In addition, the values of complexity index were significantly lower in the patients with non-AF stroke than in the controls (25.8±.3 vs 32.3±4.3, p<0.001). After adjustment for clinical variables, patients without AF who had a favourable outcome were significantly related to higher complexity index values (OR=1.15, 95% CI 1.07 to 1.25, p<0.001). Importantly, the area under the receiver operating characteristic curve for predicting a favourable outcome of patients with non-AF stroke from clinical parameters was 0.858 (95% CI 0.797 to 0.919) and significantly improved to 0.903 (95% CI 0.853 to 0.954) after adding on the parameter of complexity index values (p=0.020). Conclusions: In ICU-admitted patients with acute stroke, early assessment of the complexity of HRV by MSE can help in predicting outcomes in patients without AF.